STUDI KEANEKARAGAMAN KUPU-KUPU DI BANTARAN SUNGAI BATANGHARI KOTA METRO SEBAGAI SUMBER BELAJAR BIOLOGI MATERI KEANEKARAGAMAN - Suharno Zen, Rasuane Noor (Bioedukasi Jurnal Pendidikan Biologi, 2015)
Abstract: Butterflies are insects that have a very important role in the ecosystem is as a helper in the pollination in plants. In addition butterfly can also be used as a bio-indicator to changes in environmental quality since butterflies are very sensitive to changes in the ecosystem. The existence of butterflies are under threat at this time step and extinction, this is due to the many forests are converted into other land. Diminishing forests and lands turned into settlement and agriculture. Butterfly existence will depend habitat. Butterfly habitat with the amount of food available is quite the diversity of butterflies is high.The aim of research to determine the diversity of butterflies in Batanghari River Plate in Metro City, the research method used is survey method with purporsive sampling. Butterfly collection done by sweeping follows the line transect technique is applied randomly along the 1000 m. After completion of the identification process we then held classification process. Species diversity index (H) is calculated using the Shannon-Wiener formula. Results of the study found as many as 23 species of butterflies of 5 familia, with the most dominant species is Eurema alitha as much as 136. The diversity of butterflies in the Batanghari River Plate in City Metro categorized bit or lower because it has the value H1 <1.